Joint development in the South China sea: China's incentives and policy choices. Issue 2 (3rd July 2019) - Qi, Huaigao
ABSTRACT: Since 2017, China has actively proposed a number of joint development schemes in the South China Sea (SCS), namely with the Philippines and Vietnam. Both economic and strategic incentives lie behind China's development of these schemes. China's economic incentives include its domestic demand for energy, "21st Century Maritime Silk Road" construction, Hainan the pilot free trade zone construction, construction of a common market and the future economic integration among the SCS coastal States. China's strategic incentives include achieving its goal of becoming a leading maritime power, playing its constructive role in maintaining a peaceful and stable SCS, developing good relations with other coastal States, and reducing the intensity of China-U.S. competition in the SCS. China's policy choices on the SCS joint development are as follows: first, to promote good faith in the SCS; second, to limit unilateral activities in disputed areas; third, to focus on less sensitive areas of the SCS; fourth, to reach joint development arrangements by establishing relevant working mechanism; fifth, to begin the process in areas where there are only two claimants; sixth, to define sea areas for the joint development by seeking consensus; seventh, to discuss the feasibility of setting up a Spratly Resource Management Authority (SRMA) with supranational character.